Length and Diameter of the Cystic Duct: A Postmortem Study - Nahar, Nurun; Ara, Shamim; Rahman, Mushfika; Afroz, Halima (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15278 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.89-92